PERLINDUNGAN HUKUM BAGI KONSUMEN YANG MENGGUNAKAN PRODUK KOSMETIK PALSU - Diamanda, Agung Mira; Oka Parwata, Anak Agung Gede (Kertha Semaya : Journal Ilmu Hukum, 2020)
The rise of cosmetic products in the market makes consumers  interest in cosmetics every year. This opportunity is a great chance for the business actor who are not responsible for producing fake cosmetic products. This has caused unrest for consumers who feel their rights have been harmed . This papper aim to find out abot the legal protections for consumers who used fake cosmetic products and how businessmen responsibility for faked cosmetics products distributed to the public. The method of writing is used in this journal is normative juridical. The results showed that business actors producing fake cosmetic products have against the article number 4 of Consumer Protection Act and must be held responsible for their actions , the liability of business actors for fake cosmetic products can be carried out by way of compensation under the article number 19 of Consumer Protection Act .   Keywords : Consumer Protection, Fake Cosmetic